Composite metal magnetic body and inductor, and method for manufacturing composite metal magnetic body and method for manufacturing inductor

CN122996490APending Publication Date: 2026-10-27MURATA MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580021181.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-17
Filing Date
2025-03-25
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0013]根据本公开的复合金属磁性体,能够提高磁特性。具体而言,由于X射线衍射中存在来自FeAl相的峰和来自FeNi相的峰,并且金属磁性粒子在内部具有Al凝聚而成的Al凝聚区域,因此FeAl相使FeNi相的晶格常数增大,能够减少表观磁致伸缩。因此,能够提高复合金属磁性体的磁特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996490A_ABST
    Figure CN122996490A_ABST
Patent Text Reader

Abstract

The present application provides a composite metal magnetic body capable of improving magnetic properties, an inductor, and a manufacturing method for the composite metal magnetic body and the inductor. The composite metal magnetic body CP of the present disclosure has metal magnetic particles DP containing Fe, Ni, and Al, and an insulating coating (oxidation coating OL) covering the metal magnetic particles DP, and is formed by a plurality of metal magnetic particles DP being combined by the insulating coating, the metal magnetic particles DP having an Al agglomeration region A1 formed by Al agglomeration in the interior, and having a peak from a FeAl phase and a peak from a FeNi phase in X-ray diffraction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to composite metal magnetic materials and inductors, as well as methods for manufacturing composite metal magnetic materials and inductors. Background Technology

[0002] Patent document 1 discloses an Fe-Ni alloy pressed powder magnetic core, which is used in noise filters, choke coils of switching power supplies, etc. As a component of Fe-Ni alloy powder, it contains Ni: 70-85% by weight.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 62-99401 Summary of the Invention

[0006] Ni is rarer and more expensive than Fe, and its large-scale use could lead to increased manufacturing costs. On the other hand, reducing the Ni content could be considered, but this might result in a decrease in magnetic properties such as permeability.

[0007] In view of the above, the purpose of this disclosure is to provide a composite metal magnetic body and an inductor capable of improving magnetic properties, as well as a method for manufacturing the composite metal magnetic body and the inductor.

[0008] The composite metallic magnetic material disclosed herein comprises metallic magnetic particles containing Fe, Ni, and Al, and an insulating film covering the aforementioned metallic magnetic particles, wherein multiple of the aforementioned metallic magnetic particles are bonded together through the aforementioned insulating film or resin.

[0009] The aforementioned metallic magnetic particles have Al condensation regions formed by Al condensation inside, and in X-ray diffraction, there are peaks from the FeAl phase and peaks from the FeNi phase.

[0010] The inductor disclosed herein possesses the aforementioned composite metallic magnetic material.

[0011] The manufacturing method of the above-mentioned composite metallic magnetic material disclosed herein includes the following heat treatment step: heating the above-mentioned metallic magnetic particles in a low oxygen atmosphere or a reducing atmosphere at 400°C to 1000°C to form an insulating film mainly composed of oxides on the surface of the above-mentioned metallic magnetic particles, wherein the oxides contain Al oxides.

[0012] The manufacturing method of the inductor disclosed herein includes the following heat treatment step: heating the aforementioned metal magnetic particles in a low-oxygen atmosphere or a reducing atmosphere at 400°C to 1000°C to form an insulating film mainly composed of oxides on the surface of the aforementioned metal magnetic particles, wherein the oxides contain Al oxides.

[0013] According to the composite metallic magnetic material disclosed herein, magnetic properties can be improved. Specifically, since peaks from the FeAl phase and peaks from the FeNi phase exist in X-ray diffraction, and the metallic magnetic particles have Al condensation regions formed by Al condensation inside, the FeAl phase increases the lattice constant of the FeNi phase, thereby reducing apparent magnetostriction. Therefore, the magnetic properties of the composite metallic magnetic material can be improved. Attached Figure Description

[0014] Figure 1 This is a three-dimensional diagram of the inductor disclosed herein.

[0015] Figure 2 This is an exploded perspective view of the inductor disclosed herein.

[0016] Figure 3 It is along Figure 2 The cross-sectional view in the direction of the arrow on line III-III.

[0017] Figure 4 This is a table showing the results of the verification test.

[0018] Figure 5 This is a photograph showing the results of wavelength dispersive X-ray fluorescence analysis.

[0019] Figure 6 This is a graph showing the results of X-ray diffraction measurements.

[0020] Figure 7 This is a graph showing the relationship between the Al mix ratio and the coercivity Hc.

[0021] Figure 8 This is a graph showing the relationship between the peak position of FeNi and the coercivity Hc. Detailed Implementation

[0022] The following provides a detailed description of the composite metal magnetic body and inductor of this disclosure, as well as the manufacturing methods of the composite metal magnetic body and the inductor. Although the description is based on the accompanying drawings as needed, the illustrations are schematic and exemplary only for the purpose of understanding this disclosure, and the appearance, size, and proportions may differ from the actual objects.

[0023] <Description of the Composite Metal Magnetic Material of this Disclosure>

[0024] First, the composite metallic magnetic material CP of this disclosure will be described. It should be noted that the term "composite metallic magnetic material" as used in this specification refers to... Figure 3 The diagram shows how the metallic magnetic particles DP are bonded together by metallic magnetic powder MP, which is composed of an insulating film (oxide film OL) covering the particles DP.

[0025] Metallic magnetic powder (MP) comprises metallic magnetic particles (DP) and an insulating film (oxide film (OL)). It should be noted that the insulating film can also contain resin components through the method of forming the insulating film.

[0026] The average particle size of the metallic magnetic particles (DP) is preferably 0.2 μm to 20 μm, more preferably 0.5 μm to 15 μm, and even more preferably 1 μm to 6 μm. Such an average particle size enables the achievement of high permeability and low iron loss.

[0027] The average particle size of the metallic magnetic particles DP can be determined by the following steps. An inductor sample is cut to obtain a sample cross-section. Specifically, the sample cross-section is obtained by cutting through the center of the blank and the winding axis of the coil, orthogonally to the mounting surface and end face of the blank. It should be noted that the sample cross-section can be made into a flat surface by methods such as ion milling. For the obtained cross-section, SEM images (approximately 1000x magnification) are taken at any three positions in the center of the cut surface corresponding to the center of the blank 10, and compositional analysis is performed using EDX. Based on the compositional analysis results based on EDX, the position of Fe in the field of view is confirmed, thereby determining the position of the metallic magnetic particles DP in the SEM image. Then, in each field of view, at any three positions in the center, the confirmed metallic magnetic particles DP in the obtained SEM image are analyzed using image analysis software (e.g., WinROOF2021 image analysis software (manufactured by Mitani Corporation)) to determine the circular equivalent diameter of the metallic magnetic particles. The average value of the obtained circular equivalent diameters is taken as the average particle size of the metallic magnetic particles. It should be noted that the average particle size mentioned in this specification may refer to the average particle size D50 (the particle size corresponding to a cumulative percentage of 50% on a volume basis).

[0028] The metallic magnetic particles DP contain at least Fe, Ni, and Al elements. The metallic magnetic particles DP are described in detail in the manufacturing method description and may also be included in the magnetic paste. It should be noted that the resin component contained in the magnetic paste may disappear through heat treatment, or it may remain.

[0029] The metallic elements (Fe, Ni, and Al) constituting the heat-treated metallic magnetic particles DP can be determined using a wavelength dispersive X-ray fluorescence analyzer (JEOL Ltd., model JXA-8530F). The determination can be performed using the steps described below. Preparation of the blank 10 (refer to...) Figure 1A cut surface is formed on the mounting surface (first main surface 11) of the coil spool at a position passing through the coil spool, along the length direction of the blank 10 and in the thickness direction. On this cut surface, a 600,000x TEM is used to image the coil spool portion with metallic magnetic particles (DP) falling into the field of view, determining the position of the DP particles. At this determined position, a wavelength dispersive X-ray fluorescence analyzer is used to quantitatively analyze the metallic elements. The quantitative analysis results are described in the embodiments described later, and the obtained results are as follows: Figure 4 The analysis results are shown.

[0030] Furthermore, based on the analysis results using a wavelength dispersive X-ray fluorescence spectrometer, the metallic magnetic particles DP contain an Al condensation region A1 formed by Al condensation (refer to...). Figure 5 The term "Al condensation region" as used in this specification refers to... Figure 4 The analytical results shown indicate that the Al concentration in Al condensation region A1 is more than 1.5 times that in the outer region A2. Specifically, in Figure 4 In the study, it was confirmed that the Al concentration in the outer region A2 of the Al condensation zone was less than about 100 LEVEL, while the Al concentration in the Al condensation zone A1 was more than 150 LEVEL.

[0031] Furthermore, the metallic magnetic particles DP contain FeAl and FeNi phases. These phase compositions can be determined using an X-ray diffraction apparatus (manufactured by Rigaku Corporation, model SmartLab). The determination can be performed using the steps described below. Preparation is carried out from blank 10 (refer to...) Figure 1 The mounting surface (first main surface 11) of the blank 10 is cut along the length direction of the blank 10 and the thickness direction at the position passing through the coil spool. X-rays are irradiated onto the position of the metallic magnetic particles DP on this cut surface, and an θ-2θ scan is performed in conjunction with maintaining the X-ray incident angle relative to the measurement position and the detector angle at a ratio of 1:2. Through this measurement, the following results are obtained: Figure 5 The diffraction pattern shown has the diffraction angle on the horizontal axis and the diffraction intensity on the vertical axis. It should be noted that... Figure 5 In order to make the state of the metallic magnetic particles easier to observe, a sample made by taking a metallic magnetic particle from a sample cross section prepared by the previously described method and fixing it with resin is used.

[0032] According to the analysis results of wavelength dispersive X-ray fluorescence spectrometry and the measurement results of X-ray diffraction, the heat-treated metallic magnetic particles DP contain Al condensation regions Al1 formed by Al condensation. In X-ray diffraction, peaks from the FeAl phase and peaks from the FeNi phase are observed. Therefore, the FeAl phase increases the lattice constant of the FeNi phase, which can reduce the apparent magnetostriction of the composite metallic magnetic body. Thus, the composite metallic magnetic body of this disclosure can improve its magnetic properties. Detailed effects will be described in the embodiments described later.

[0033] As a preferred method for the proportion of metal elements in the magnetic particles DP, based on the metal elements contained in the magnetic particles DP, Fe can be 46wt% to 92wt%, Ni can be 6wt% to 50wt%, and Al can be 2wt% to 7wt%. In other words, when the metal elements constituting the magnetic particles DP are Fe, Ni, and Al, and these metal elements are set to a total of 100wt%, Fe can be 46wt% to 92wt%, Ni can be 6wt% to 50wt%, and Al can be 2wt% to 7wt%. It should be noted that the magnetic particles DP may also contain impurities of elements that are unavoidable during manufacturing. With such a proportion, at least the content of Ni element can be reduced compared to the past, and the magnetic properties can be improved as described in the embodiments described later while reducing manufacturing costs.

[0034] Furthermore, as a preferred manner for the Al condensation region A1 of the metallic magnetic particle DP, the Al condensation region A1 may exist locally within the metallic magnetic particle DP. The term "locally exist" in this specification means that the Al condensation region A1 exists at a specific location within the metallic magnetic particle DP. If we define the manner in which this Al condensation region A1 is determined using another expression, it would be as follows: Figure 5 As shown, in a cross-sectional view of the metallic magnetic particle DP, the cross-sectional area of ​​the Al condensation region A1 can be 1% to 20% of the total cross-sectional area of ​​the metallic magnetic particle DP. If the Al condensation region A1 is in this manner, the magnetic properties can be improved as described in the embodiments below.

[0035] The surface of the aforementioned metallic magnetic particles DP is covered by an insulating film (oxide film OL). The term "insulation" as used in this specification refers to a volume resistivity of 1 MΩ·cm or higher. Covering the surface of the metallic magnetic particles DP with an insulating film improves the insulation between the particles. A specific example of an insulating film is... Figure 3As shown, an oxide film OL is formed. Adjacent metallic magnetic particles DP are bonded together by this oxide film OL. It should be noted that a resin R exists between the oxide films OL of the metallic magnetic particles DP bonded by the oxide film OL. It should be noted that the resin R is an epoxy resin as described below, but may also be one or more resins selected from phenolic resins, polyester resins, polyimide resins, polyolefin resins, silicone resins, acrylic resins, polyvinyl butyral resins, cellulose resins, and alkyd resins.

[0036] The oxide coating OL is a film formed by oxidizing metallic magnetic particles DP through heat treatment. That is, it can contain oxygen. Furthermore, as an example, the oxide coating OL can contain oxides of Al contained in the metallic magnetic particles DP. In other words, the oxide coating OL can contain oxides primarily composed of Al oxides, or oxides of Al and Fe, or composite oxides thereof (i.e., aluminum oxide, FeAl₂O₄, etc., and their composite oxides). By employing an Al oxide coating, high insulation reliability can be achieved.

[0037] The thickness of the oxide film OL is preferably 5 nm to 100 nm, more preferably 5 nm to 50 nm, and even more preferably 5 nm to 20 nm. The thickness of the oxide film OL can be determined, for example, by photographing a cross-section obtained by grinding an inductor sample using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and the thickness of the oxide film OL covering the surface of the metallic magnetic particles DP can be measured based on the obtained SEM images. It should be noted that the thickness of the oxide film OL is measured as follows: Images are taken at any three positions in the center of a cut surface that passes through the center of the blank and the winding shaft of the coil and is orthogonal to the mounting surface and end face of the blank. In each field of view, the thickness of the oxide film OL is measured at any three positions in the center. The thickness of the oxide film OL is calculated by averaging the results of (any three positions in the center of the cut surface) × (any three positions in the center of each field of view) = 9 positions.

[0038] The oxide coating OL is described in detail in the method for manufacturing the composite metallic magnetic material described later, and can also be formed by calcination in a low-oxygen atmosphere or a reducing atmosphere. The low-oxygen atmosphere referred to in this specification is an atmosphere with an oxygen concentration of 2 ppm to 200 ppm. Furthermore, a reducing atmosphere is an atmosphere in which the reaction of removing oxygen from a substance occurs. It should be noted that, as explained in the examples described later, calcination in an air atmosphere cannot form DP in the metallic magnetic particles. Figure 5 The Al agglomeration region A1 is shown. Furthermore, according to the coercivity measurement described in the later examples, the measurement was beyond the specified range and could not be performed.

[0039] Resin R can be used to improve the strength of the inductor blank, as described later. As an example, in the magnetic layers G1 to G8 (refer to...) described later... Figure 2 After heat treatment of the laminated preform 10, the preform 10 is impregnated with resin, thereby allowing it to exist between adjacent metallic magnetic powders MP bonded by an oxide film OL. As an example, epoxy resin or silicone resin can be used as the resin impregnated after heat treatment of the preform 10. Other resins may be selected from one or more resins such as phenolic resin, polyester resin, polyimide resin, polyolefin resin, acrylic resin, polyvinyl butyral resin, cellulose resin, and alkyd resin.

[0040] <Description of the inductor disclosed herein>

[0041] Next, refer to Figure 1 and Figure 2 The inductor of this disclosure will be described. The inductor of this disclosure includes: a blank 10 having the above-described composite metal magnetic material CP, and a coil disposed within the blank 10.

[0042] The blank 10 is, for example, a cuboid shape or a roughly cuboid shape with six faces. The corners and edges of the blank 10 may have rounded corners. The corners are the parts where three faces of the blank 10 intersect, and the edges are the parts where two faces of the blank 10 intersect.

[0043] Figure 1 In this diagram, the length, width, and height directions of the inductor 1 and the blank 10 are represented as the L direction, W direction, and T direction, respectively. The length direction L, width direction W, and height direction T are orthogonal to each other. The mounting surface of the inductor 1 is, for example, a surface parallel to the length direction L and the width direction W (LW surface).

[0044] Figure 1 The billet 10 shown has a first main surface 11 and a second main surface 12 opposite each other in the height direction T, a first end surface 13 and a second end surface 14 orthogonal to the height direction T and opposite each other in the length direction L, and a first side surface 15 and a second side surface 16 opposite each other in the width direction W orthogonal to the length direction L and the height direction T. Figure 1 In the example shown, the first main surface 11 of the billet 10 corresponds to the mounting surface (bottom surface) of the billet 10. It should be noted that the second main surface 12 can also be the mounting surface of the billet 10.

[0045] The blank 10 has a laminated structure formed by stacking multiple magnetic body layers, each having a magnetic layer ML and a coil conductor CD, in a stacking direction (e.g., height direction T). In this embodiment, as... Figure 2As shown, the blank 10 is constructed by stacking magnetic layers G1 to G8. Then, a coil is constructed by stacking multiple coil conductors CD. Constructing the coil by stacking coil conductors CD facilitates miniaturization. It should be noted that the boundaries of each layer in the stacked structure of the blank 10 disappear. Furthermore, each magnetic layer G1 to G8 can be constructed by stacking multiple identical patterns.

[0046] A coil, constructed by stacking multiple coil conductors CD, is provided within the blank 10. Figure 2 In the example shown, two coils (a first coil and a second coil) are provided within the blank 10 along the stacking direction. More specifically, the first coil is constituted by the coil conductor CD of magnetic layers G4 and G5, and the second coil is constituted by the coil conductor CD of magnetic layers G2 and G3. Cu is used as the main component of the coil conductor CD. By using Cu, the inductance characteristics can be improved. It should be noted that, as an example of the material of the coil conductor CD, metal conductors such as Ag, Au, or their alloys can also be used instead of Cu. Furthermore, the inductor 1 of the first embodiment is not limited to this example; for example, three or more coils may be provided along the stacking direction. In addition, coils may also be provided inside the blank 10 in a direction intersecting the stacking direction ( Figure 1 Multiple coils are arranged side by side in the L direction to form a coil array.

[0047] An external electrode E is provided on the mounting surface (first main surface 11) of the blank 10. Figure 2 In the example shown, the external electrode E has a first external electrode E1 and a second external electrode E2, which are respectively connected to the ends of the first coil, and a third external electrode E3 and a fourth external electrode E4, which are respectively connected to the ends of the second coil. It should be noted that the number of external electrodes corresponds to two external electrodes per coil. Therefore, assuming there are three coils, the number of external electrodes would be six.

[0048] The connection between the coil and the external electrode E can use a through-hole conductor TH. That is, the first through-hole conductor TH1 to the fourth through-hole conductor TH4 can be provided corresponding to the first external electrode E1 to the fourth external electrode E4. In addition, the first through-hole conductor TH1 to the fourth through-hole conductor TH4 can be provided to extend along the stacking direction.

[0049] According to the inductor disclosed herein, by calcining in a low-oxygen atmosphere or a reducing atmosphere, an inductor can be provided that has an Al condensation region Al formed by Al condensation inside the metallic magnetic particles DP, and exhibits peaks from the FeAl phase and peaks from the FeNi phase in X-ray diffraction. Therefore, the FeAl phase increases the lattice constant of the FeNi phase, which can reduce the apparent magnetostriction of the composite metallic magnetic material.

[0050] <Methods for manufacturing composite metallic magnetic materials and inductors disclosed herein>

[0051] Next, the method for manufacturing the inductor disclosed herein will be described. It should be noted that since the method for manufacturing the composite metal magnetic material is included in the method for manufacturing the inductor, its description will be omitted.

[0052] The method for manufacturing the inductor disclosed herein includes a preparation step, a pressurization step, and a heat treatment step. It should be noted that, as described below, an optional degreasing step may be included.

[0053] -Preparation Process-

[0054] Preparation Figure 2 The magnetic material (magnetic paste) of the magnetic layers ML of the magnetic layers G1 to G8 as described above, and the conductor paste that constitutes the coil conductor CD.

[0055] As an example of a method for preparing a magnetic paste, an Fe-containing metal powder with a cumulative 50% particle size (D50) of 2 μm to 20 μm on a volume basis is prepared. Al powder (for example, Al particles: 0.1 wt% to 10 wt%) is added to this metal powder, along with a mixture containing cellulose or polyvinyl butyral (PVB) as a binder, and terpineol and butyl diethylene glycol acetate (BCA) as a solvent, and the mixture is kneaded to prepare a magnetic paste.

[0056] As a conductive paste, for example, a paste containing Cu as a conductive material can be prepared. It should be noted that the conductive material is not limited to Cu; conductive pastes made from conductive materials such as Ag, Au, or their alloys can also be used.

[0057] The magnetic paste and conductive paste described above are prepared and layered using methods such as screen printing. Figure 2 The magnetic layers G1 to G8 are shown.

[0058] -Pressure process (any additional process)-

[0059] After stacking magnetic layers G1 to G8, pressure is applied to the magnetic layers G1 to G8. This pressure application can be carried out at a pressure of 300 MPa or higher. By applying pressure to the magnetic layers G1 to G8, two or more metallic magnetic powders MP are bonded together to form a composite metallic magnetic body CP.

[0060] -Degreasing process (any additional process)-

[0061] A preferred manufacturing process for an inductor may include a degreasing step. The degreasing step removes the binders contained in the magnetic paste and conductive paste. As an example, degreasing is performed at a temperature of approximately 300°C to 500°C. This removes the binders contained in the magnetic paste and conductive paste.

[0062] -Heat treatment process-

[0063] Heat treatment is performed after the degreasing process. As an example of heat treatment conditions, nitrogen is injected into the furnace of the heat treatment apparatus at a flow rate of 19 L / min, creating a low-oxygen atmosphere within the furnace. Alternatively, as another example of heat treatment conditions, nitrogen is injected into the furnace at a flow rate of 19 L / min, and hydrogen is injected at a flow rate of 0.19 L / min, creating a reducing atmosphere within the furnace. The heat treatment temperature is determined by the degree of sintering of the coil conductor, and can be, for example, around 400°C to 1000°C. However, to balance reducing coercivity and suppressing thermal diffusion of coil conductor material components into the billet, 700°C to 900°C is preferred. Particularly when forming highly corrosion-resistant composite oxides such as FeAl₂O₄, 750°C to 900°C is preferred. This heat treatment can form an insulating film, primarily composed of Al oxides, on the surface of the metallic magnetic particles within the billet, and the insulating film bonds adjacent metallic magnetic particles together.

[0064] Furthermore, to improve the strength of the preform, resin can be impregnated into the gaps between the oxide films of adjacent metallic magnetic particles within the preform and then cured. The resin impregnated in the preform is epoxy resin, but one or more resins selected from phenolic resin, polyester resin, polyimide resin, polyolefin resin, silicone resin, acrylic resin, polyvinyl butyral resin, cellulose resin, and alkyd resin may also be used. The preform of the inductor of this disclosure is formed through the above process.

[0065] Then, external electrodes electrically connected to the coil conductors are formed on the formed blank. The external electrodes are formed by electroplating at the exposed position of the through-hole conductor on the mounting surface (first main surface 11) of the blank 10. The plating material can be a Cu plating layer. Examples of other plating materials include Ni-Sn, Ni-Au, Ni-Cu, and / or Cu-Ni-Au, but are not limited to these. The inductor of this embodiment can be manufactured by single-piece cutting after the external electrodes are formed.

[0066] As described above, the inductor manufacturing method according to this embodiment can produce an inductor having an Al condensation region Al formed by Al condensation inside the metallic magnetic particles DP, and exhibiting peaks from the FeAl phase and peaks from the FeNi phase in X-ray diffraction. Therefore, the FeAl phase increases the lattice constant of the FeNi phase, which can reduce the apparent magnetostriction of the composite metallic magnetic body.

[0067] Example

[0068] The verification tests of the composite metallic magnetic material of this disclosure will be described in detail. Specifically, the inductors described in Examples 1 to 8 and Comparative Examples 1 to 4 were manufactured.

[0069] -Description of the inductor in Example 1-

[0070] (1) A magnetic paste is prepared by mixing a metal powder containing Fe (54wt%), Ni (45wt%) and Al (1wt%) with a D50 of 5μm, which contains ethyl cellulose as a binder and a mixture of terpineol and butyl diethylene glycol acetate (BCA) as a solvent.

[0071] (2) Figure 2 As shown, after stacking magnetic layers G1 to G8, the magnetic layers are pressurized and degreased at a pressure of about 300 MPa (pressurization process and degreasing process).

[0072] (3) Heat treatment is carried out at 750°C under a reducing atmosphere (nitrogen flow rate 19 L / min, hydrogen flow rate 0.19 L / min) inside the furnace of the heat treatment device.

[0073] -Description of the inductors in Examples 2-4-

[0074] In the inductor of Example 2, the Al content of the metal powder is 3 wt%. In the inductor of Example 3, the Al content of the metal powder is 5 wt%. In the inductor of Example 4, the Al content of the metal powder is 7 wt%. It should be noted that the Ni content is the same as in Example 1. Furthermore, in the above examples, as the Al content increases, the Fe content is correspondingly reduced. Other processes are the same as in Example 1.

[0075] -Description of the inductor in Example 5-

[0076] (1) A magnetic paste is prepared by mixing a metal powder containing Fe (54wt%), Ni (45wt%) and Al (1wt%) with a D50 of 5μm, which contains ethyl cellulose as a binder and a mixture of terpineol and butyl diethylene glycol acetate (BCA) as a solvent.

[0077] (2) Figure 2 As shown, after stacking magnetic layers G1 to G8, the magnetic layers are pressurized and degreased at a pressure of about 300 MPa (pressurization process and degreasing process).

[0078] (3) Heat treatment is carried out at 700°C under a low oxygen atmosphere (nitrogen flow rate 19 L / min) inside the furnace of the heat treatment device.

[0079] -Description of the inductors in Examples 6-8-

[0080] In the inductor of Example 6, the Al content of the metal powder is 3 wt%. In the inductor of Example 7, the Al content of the metal powder is 5 wt%. In the inductor of Example 8, the Al content of the metal powder is 7 wt%. It should be noted that the Ni content is the same as in Example 5. Furthermore, in the above examples, as the Al content increases, the Fe content is correspondingly reduced. Other processes are the same as in Example 5.

[0081] -Explanation of the inductor in Comparative Example 1-

[0082] (1) A magnetic paste is prepared by mixing a metal powder containing Fe (54wt%), Ni (45wt%) and Al (1wt%) with a D50 of 5μm, which contains ethyl cellulose as a binder and a mixture of terpineol and butyl diethylene glycol acetate (BCA) as a solvent.

[0083] (2) Figure 2 As shown, after stacking magnetic layers G1 to G8, the magnetic layers are pressurized and degreased at a pressure of about 300 MPa (pressurization process and degreasing process).

[0084] (3) Heat treatment is carried out at 700°C while the furnace of the heat treatment apparatus is in an air atmosphere.

[0085] -Explanation of the inductors in Comparative Examples 2-4-

[0086] In Comparative Example 2, the Al content of the metal powder in the inductor was 3 wt%. In Comparative Example 3, the Al content of the metal powder in the inductor was 5 wt%. In Comparative Example 4, the Al content of the metal powder in the inductor was 7 wt%. It should be noted that the Ni content was the same as in Comparative Example 1. Furthermore, in all the above comparative examples, the Fe content decreased accordingly with the increase of the Al content. The other processes were the same as in Comparative Example 1.

[0087] -Inductor Evaluation 1 (Wavelength Dispersive X-ray Fluorescence Analysis)-

[0088] Wavelength dispersive X-ray fluorescence analysis was performed on the inductors of Examples 1-8 and Comparative Examples 1-4. The specific analytical procedures are as described in the above description of the composite metallic magnetic body of this disclosure. As an example of the analytical results, Figure 5 The analysis results for the inductor of Example 3 are shown. It should be noted that... Figure 5 The results are shown from left to right as <Al analysis results>, <Fe analysis results>, and <Ni analysis results>.

[0089] according to Figure 5 The Al analysis results confirm the presence of a localized Al condensation region A1 with an Al concentration of approximately 150 LEVEL or higher. Furthermore, it is confirmed that the Al concentration in Al condensation region A1 (approximately 150 LEVEL) is more than 1.5 times that of the Al concentration in the outer region A2 (less than approximately 100 LEVEL).

[0090] On the other hand, the inductors in Comparative Examples 1 to 4 do not exhibit the characteristics seen in the former. Figure 5 The Al condensation region A1 is shown.

[0091] -Inductor Evaluation 2 (X-ray Diffraction)-

[0092] X-ray diffraction measurements were performed on the inductors of Examples 1-8 and Comparative Examples 1-4. The specific measurement procedures are as described in the above description of the composite metallic magnetic body of this disclosure. As an example of the measurement results, Figure 6 The measurement results of the inductors of Example 4, Example 8 and Comparative Example 4 are shown.

[0093] according to Figure 6 The measurement results showed that peaks from the FeAl phase and peaks from the FeNi phase could be identified in the inductors of Examples 1 to 8. On the other hand, peaks from the FeAl phase and peaks from the FeNi phase could not be identified in the inductors of Comparative Examples 1 to 4.

[0094] -Inductor Evaluation 3 (Measurement of Magnetic Properties (Coercivity Hc))-

[0095] The magnetic properties (coercivity Hc) of the inductors of Examples 1-8 and Comparative Examples 1-4 were measured. Specifically, an automatic coercivity measuring device (manufactured by Tohoku Special Steel, model: K-HC1000) was used to measure the coercivity Hc by applying a standard magnetic field (1850 Oe (Oersted)). It should be noted that in this measurement, the smaller the value of the coercivity Hc, the smaller the area of ​​the DC hysteresis loop, the smaller the hysteresis loss, and the greater the permeability. Therefore, the smaller the Hc, the better the inductance characteristics.

[0096] The coercivity Hc of the inductors in Comparative Examples 1-4 exceeded the measurement range and could not be measured. On the other hand, it was found that the coercivity Hc of the inductors in Examples 1-8 was lower than that of the inductors in Comparative Examples 1-4 (see reference). Figure 6 and Figure 7 ).

[0097] Furthermore, it was found that the coercivity Hc of inductors calcined in a reducing atmosphere (Examples 1-4) was lower than that of inductors calcined in a low-oxygen atmosphere (Examples 5-8).

[0098] Additionally, considering the results of "-Evaluation of Inductors 2 (X-ray Diffraction)-" above, based on the peak position of the FeNi peak with the horizontal axis as the reference point ( Figure 6 The graph shows the peak position near 74.73° (vertical axis is the coercivity Hc). Figure 8 The results showed that changing the Al content caused a peak shift in the FeNi phase. This peak shift indicates that changing the Al content in the metallic magnetic particles increases the lattice constant of the FeNi phase. In other words, it means that the FeAl phase increases the lattice constant of the FeNi phase. As a result, apparent magnetostriction can be reduced, and the magnetic properties of the composite metallic magnetic material can be improved. In other words, the magnetic properties can be improved while reducing the Ni content in metallic magnetic particles containing Fe, Ni, and Al.

[0099] The present disclosure includes a composite metal magnetic material and an inductor, as well as a method for manufacturing the composite metal magnetic material and the inductor.

[0100] <1> A composite metallic magnetic body comprising metallic magnetic particles containing Fe, Ni, and Al, and an insulating film covering the metallic magnetic particles, wherein a plurality of the metallic magnetic particles are bonded together through the insulating film.

[0101] The aforementioned metallic magnetic particles have Al condensation regions formed by Al condensation inside, and in X-ray diffraction, there are peaks from the FeAl phase and peaks from the FeNi phase.

[0102] <2> According to <1> the composite metal magnetic body, wherein the insulating film is mainly composed of oxide, and the oxide contains Al oxide.

[0103] <3> According to <2>, the composite metal magnetic material, wherein the oxide is FeAl2O4.

[0104] <4> The composite metal magnetic body according to any one of <1> to <3>, wherein the average particle size of the metal magnetic particles is 1 μm to 6 μm.

[0105] <5> The composite metallic magnetic body according to any one of <1> to <4>, wherein the Al condensation region is locally present within the metallic magnetic particles.

[0106] <6> An inductor comprising any one of <1> to <5> composite metallic magnetic body.

[0107] <7> A method for manufacturing a composite metallic magnetic material, which is the method for manufacturing a composite metallic magnetic material as described in any one of <1> to <5>, comprising the following heat treatment steps:

[0108] The aforementioned metallic magnetic particles are heated at 400°C to 1000°C in a low-oxygen atmosphere or a reducing atmosphere to form an insulating film mainly composed of oxides on the surface of the metallic magnetic particles, wherein the oxides contain Al oxides.

[0109] <8> The method for manufacturing the composite metal magnetic body according to <7>, wherein the oxide is FeAl2O4.

[0110] <9> A method for manufacturing an inductor, which is the method for manufacturing an inductor described in <6>, includes the following heat treatment step:

[0111] The aforementioned metallic magnetic particles are heated at 400°C to 1000°C in a low-oxygen atmosphere or a reducing atmosphere to form an insulating film mainly composed of oxides on the surface of the metallic magnetic particles, wherein the oxides contain Al oxides.

[0112] <10> The manufacturing method of the inductor according to <9>, wherein the oxide is FeAl2O4.

[0113] Industrial availability

[0114] The composite metal magnets and inductors disclosed herein, as well as their manufacturing methods, can preferably be used in the form of electronic components capable of improving magnetic properties.

[0115] Symbol Explanation

[0116] 1. Inductor

[0117] 10. Green body

[0118] 11 First Main Face

[0119] 12 Second Main Face

[0120] 13 First end face

[0121] 14 Second end face

[0122] 15 First side view

[0123] 16 Second side view

[0124] A1 Al condensation region

[0125] The outer side of the A2 Al condensation region

[0126] C coil

[0127] CD coil conductor

[0128] CP composite metallic magnetic material

[0129] DP metallic magnetic particles

[0130] E External Electrode

[0131] E1~E4 First external electrode~Fourth external electrode

[0132] G1~G8 Magnetic layers

[0133] ML magnetic layer

[0134] MP Metal Magnetic Powder

[0135] OL oxide coating

[0136] R resin

[0137] TH through-hole conductor

[0138] TH1~TH4 First through-hole conductor~Fourth through-hole conductor

Claims

1. A composite metallic magnetic material comprising metallic magnetic particles containing Fe, Ni, and Al, and an insulating film covering the metallic magnetic particles, wherein a plurality of the metallic magnetic particles are bonded together through the insulating film. The metallic magnetic particles have Al condensation regions formed by Al condensation inside, and in X-ray diffraction, there are peaks from the FeAl phase and peaks from the FeNi phase.

2. The composite metallic magnetic body according to claim 1, wherein, The insulating film is mainly composed of oxides, and the oxides contain Al oxides.

3. The composite metallic magnetic material according to claim 2, wherein, The oxide is FeAl2O4.

4. The composite metallic magnetic body according to any one of claims 1 to 3, wherein, The average particle size of the metallic magnetic particles is 1 μm to 6 μm.

5. The composite metallic magnetic body according to any one of claims 1 to 4, wherein, The Al condensation region exists locally within the metallic magnetic particles.

6. An inductor comprising the composite metallic magnetic body according to any one of claims 1 to 5.

7. A method for manufacturing a composite metallic magnetic material, as described in any one of claims 1 to 5, comprising the following heat treatment steps: The metallic magnetic particles are heated at 400°C to 1000°C in a low-oxygen atmosphere or a reducing atmosphere to form an insulating film mainly composed of oxides on the surface of the metallic magnetic particles, wherein the oxides contain Al oxides.

8. The method for manufacturing the composite metallic magnetic material according to claim 7, wherein, The oxide is FeAl2O4.

9. A method for manufacturing an inductor, the method for manufacturing an inductor according to claim 6, comprising the following heat treatment step: The metallic magnetic particles are heated at 400°C to 1000°C in a low-oxygen atmosphere or a reducing atmosphere to form an insulating film mainly composed of oxides on the surface of the metallic magnetic particles, wherein the oxides contain Al oxides.

10. The method for manufacturing an inductor according to claim 9, wherein, The oxide is FeAl2O4.

Citation Information

Patent Citations

  • Fe-ni alloy green compact magnetic core

    JP1987099401A